Reproduksi Phaleria spp. di Kebun Raya Bogor dan Upaya Konservasinya: Reproduction Habits of Phaleria spp. at Bogor Botanic Garden, One Step Towards its Conservation - Syamsul Hidayat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2009)
Reproduction Habits (Flowering, Fruitting and germination) of Phaleria spp. at Bogor Botanical Garden, One Step Towards Its Conservation. Phaleria is potensial genus for ornamental and medicinal plant. This genus consist of 38 species in the world, of which distributed in Indonesia particularly in Sulawesi and Papua, three of them are conserved at Bogor Botanical Garden. In some countries, the plants have been used for medical treatments, craft, food sources, and ornamental plant. As a preliminary research for the next conservation effort, an evaluating of flowering/fruitting season and generation growth of Phaleria collection was studied. The reason of the research, there is no many seed on the garden grow as a seedling. So the germination studied on the nuresry. The result show tahat January to March as a peak season for flowering/fruitting of Phaleria. The germination rate is very fantastic, 10% of seed have been germinated one day after planted. The result also shows that the fallen seed have germinated higher than picked seed. A thick manure on the land and low sunlight penetration might be the problems on the garden for growing seedling of Phaleria. Keywords: Phaleria, flowering/fruitting season, germination, and conservation.